Genome‐wide mRNA profiling identifies RCAN1 and GADD45A as regulators of the transitional switch from survival to apoptosis during ER stress. (10th January 2020) - Bartoszewski, Rafal; Gebert, Magdalena; Janaszak‐Jasiecka, Anna; Cabaj, Aleksandra; Króliczewski, Jarosław; Bartoszewska, Sylwia; Sobolewska, Aleksandra; Crossman, David K.; Ochocka, Renata; Kamysz, Wojciech; Kalinowski, Leszek; Dąbrowski, Michał; et al.
Abstract : Endoplasmic reticulum (ER) stress conditions promote a cellular adaptive mechanism called the unfolded protein response (UPR) that utilizes three stress sensors, inositol‐requiring protein 1, protein kinase RNA‐like ER kinase, and activating transcription factor 6. These sensors activate a number of pathways to reduce the stress and facilitate cell survival. While much is known about the mechanisms involved that modulate apoptosis during chronic stress, less is known about the transition between the prosurvival and proapoptotic factors that determine cell fate. Here, we employed a genetic screen that utilized three different pharmacological stressors to induce ER stress in a human‐immortalized airway epithelial cell line, immortalized human bronchial epithelial cells. We followed the stress responses over an 18‐h time course and utilized real‐time monitoring of cell survival, next‐generation sequencing, and quantitative real‐time PCR to identify and validate genes that were upregulated with all three commonly employed ER stressors, inhibitor of calpain 1, tunicamycin, and thapsigargin. growth arrest and DNA damage‐inducible alpha ( GADD45A ), a proapoptotic factor, and regulator of calcineurin 1 ( RCAN1 ) mRNAs were identified and verified by showing that small interfering RNA (siRNA) knockdown of GADD45A decreased CCAAT‐enhancer‐binding protein homologous protein (a.k.a DDIT3 ), BCL2‐binding component 3 (a.k.a. BBC3), and phorbol‐12‐myristate‐13‐acetate‐induced protein 1 expression, 3 proapoptotic factors, and increased cell viability during ER stress conditions, whereas siRNA knockdown of RCAN 1 dramatically decreased cell viability. These results suggest that the relative levels of these two genes regulate cell fate decisions during ER stress independent of the type of ER stressor. Abstract : ER stress is known to initiate a cellular adaptive mechanism called the unfolded protein response (UPR), which promotes cell survival or, under conditions of unmitigated stress, triggers cell death. The transitional regulation of cell fate is not well understood. Here, Rafal Bartoszewski and co‐authors used genome‐wide mRNA profiling to identify genes involved in directing the switch between prosurvival and proapoptotic factors during ER stress. They pinpointed two genes, GADD45A and RCAN1, as key transitional regulators of cell fate in a number of human cell lines.